Distribution profile and availability of Cr, Ni, Cu, Cd and Pb in different sediments from anhumas surface water collection reservoir, Araraquara-São Paulo State, Brazil - Santos, A. [UNESP]; Rocha, J. C. [UNESP]; Rezende, M. O.O. [UNESP]; Rosa, A. H.; Sargentini, É (My University, 2002)
In this work the influence of the anhtropogenic activities in the uptake of metals at a reservoir for public water supply in Araraquara City, São Paulo State, Brazil was studied. For this, the distribution of Cr, Ni, Cu, Cd and Pb in sediments collected from Anhumas reservoir, at seven sampling points and at three depths for each point was investigated. The pseudo-total and available metals contained in the different sediment samples were assessed using an ICP-AES technique. Among the five metals studied, cadmium possesses the largest relative potential availability, with percentages of 20 to 98% for the three different sediment types. In addition, the following decreasing availability order was characterized: Cd > Cu > Pb > Ni > Cr.
Keywords: Atomic emission spectrometry; Heavy metals; Sediment